2017
DOI: 10.1371/journal.pone.0186224
|View full text |Cite
|
Sign up to set email alerts
|

Specvis: Free and open-source software for visual field examination

Abstract: Visual field impairment affects more than 100 million people globally. However, due to the lack of the access to appropriate ophthalmic healthcare in undeveloped regions as a result of associated costs and expertise this number may be an underestimate. Improved access to affordable diagnostic software designed for visual field examination could slow the progression of diseases, such as glaucoma, allowing for early diagnosis and intervention. We have developed Specvis, a free and open-source application written… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A common challenge when validating two visual field tests against each other is that they rarely probe the exact same locations in space (see, for example, Dzwiniel et al ., and Koiava et al ., for other studies that have faced the same challenge). The Esterman test covers an oval space, vertically spanning 30 degrees of visual angle superior, 60 degrees inferior, and horizontally spanning 160 degrees.…”
Section: C‐vft and Esterman Testmentioning
confidence: 88%
See 2 more Smart Citations
“…A common challenge when validating two visual field tests against each other is that they rarely probe the exact same locations in space (see, for example, Dzwiniel et al ., and Koiava et al ., for other studies that have faced the same challenge). The Esterman test covers an oval space, vertically spanning 30 degrees of visual angle superior, 60 degrees inferior, and horizontally spanning 160 degrees.…”
Section: C‐vft and Esterman Testmentioning
confidence: 88%
“…However, most of these run online (e.g., Koiava et al ., and Olsen et al ., ) and thus require a stable Internet connection to work as intended. Other programs, while giving excellent information on the patient's visual field, are harder to complete for the patients or harder to administer for the examiner (e.g., Dzwiniel et al ., ). Test selection and the interpretation of results often require in‐depth knowledge about visual perception, detailed knowledge about visual field assessment techniques, as well as advanced computer skills.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of these novel ideas, the concept of usage of a personal computer (PC) screen for automated perimetry and as a screening device for visual field defects was given by Dzwiniel et al after an internal validation study in the form of a free and open-source software called Specvis, having the capability to run on almost all types of popular PCs irrespective of its manufacturer or operating system. Although the internal validation revealed that the software can be used as a reliable visual field examination tool, the study was limited by a small sample size including only four glaucoma patients, and comparison to only Medmont M700 Automated Static Perimeter [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This software could be of potential application by assisting the clinicians in quick evaluation or optimization of the radiotherapy treatment plans. For testing visual field impairment, a free and open-source application (Specvis), written in Java programming language has been developed and tested on glaucomatous, retinitis pigmentosa and stroke patients [ 28 ]. The main advantages of Specvis over existing methods are its free availability, affordability, and reliability in parallel to high-cost solutions.…”
Section: Introductionmentioning
confidence: 99%